2014
DOI: 10.4103/2278-330x.136792
|View full text |Cite
|
Sign up to set email alerts
|

Survival outcome of malignant minor salivary tumors in Pakistani population

Abstract: Objective:Malignant tumors of minor salivary glands (MSG) are rare. Survival outcome in Pakistani population with malignant MSG tumors remains to be defined. The objective of this study was to report the clinical presentation, treatment modalities, and survival outcome of radically treated malignant tumors of MSG in Pakistani population.Materials and Methods:Between April 2003 and March 2011, 45 patients with malignant tumors of MSG were treated at Shaukat Khanum Cancer Hospital and included in the study. Pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Antti Mäkitie and Leif Bäck have contributed equally ACC is denoted as the second most common malignancy [2]. Some nationwide studies from Finland, Denmark, and Pakistan, however, have reported that the most common salivary gland cancer in those countries is ACC [3][4][5].…”
Section: Karoliina Hirvonen Shared First Authorshipmentioning
confidence: 99%
“…Antti Mäkitie and Leif Bäck have contributed equally ACC is denoted as the second most common malignancy [2]. Some nationwide studies from Finland, Denmark, and Pakistan, however, have reported that the most common salivary gland cancer in those countries is ACC [3][4][5].…”
Section: Karoliina Hirvonen Shared First Authorshipmentioning
confidence: 99%
“…The remaining 1496 abstracts were screened for eligibility, yielding 131 manuscripts. Their full text evaluation identified 64 studies meeting the inclusion criteria 17–80 …”
Section: Resultsmentioning
confidence: 99%
“…Eighteen studies (28.1%) analyzed 946 primary minor SGCs and reported treatment of 426 recurrences (45.0%) 20–22,26,27,32–34,40,44,47,50,52,56,63,67,76 . Twenty‐five articles (39.1%) analyzed 1568 primary major SGCs and reported treatment of 570 recurrences (36.3%) 17,25,31,35,36,38,40,41,42,45,46,49,57,59,60,62,64,68,69,71,73,75,77–79 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While inconsistent findings were reported by Iqbal H. et. al 8. Although demographic data from few studies countrywide, gives an insight of the biological and clinical characteristics of the tumours in head and neck region.…”
mentioning
confidence: 99%